Economic benefits from the coordinated control of Distributed Energy Resources and different Charging Technologies of Electric Vehicles in a Smart Microgrid. (July 2017) - Anastasiadis, Anestis G.; Kondylis, Georgios P.; Vokas, Georgios A.; Konstantinopoulos, Stavros A.; Salame, Chafic-Touma; Polyzakis, Apostolos; Tsatsakis, Konstantinos
Abstract: In the near future, Electric Vehicles (EVs') penetration is expected to rise, making the study of their local level effects imperative. EVs is a new, promising, technology which will offer cleaner and more effective means of transportation. On the other hand, EVs can also act as storage devices, thus offering ancillary services to the grid. The optimum operation of Low Voltage (LV) grids, with special emphasis on Smart Microgrids (SM), must be ensured and the financial viability of EVs' penetration is to be assessed. Smart Microgrids seem to be the best solution for the management of modern LV grids with Distributed Energy Resources (DER). The main purpose of this paper is to investigate the economic benefits that can arise from the coordinated control of DER and EVs in SM operation. Absence of distributed resources, and therefore satisfaction of the full load from the upstream network, is considered as the base case. Various pricing policies based on System Marginal Prices (SMPs) are considered. For each scenario, three different charging technologies are examined. All different cases are compared between them to determine which one is the most advantageous in terms of operational cost.